Crystallization and structure elucidation of recombinant Pseudomonas aeruginosa strain K solvent tolerant elastase - Mat Said, Zatty Syamimi@Adura (2014)
The discoveries of elastase that actively catalyse a variety of reaction in both aqueous and non-aqeous/ organic solvent are among the most important biocatalysts that constantly being sought by enzymologies. Elastase represents a class of enzyme which occupies a pivotal position with respect to their physiological role as well as commercial applications. The degradation and synthetic reaction are being more efficient with intervention of elastase. The unique properties owned by elastase become an interest to understand the three-dimensional structure of the enzyme. However, little is known on the elastase structure and function particulary tolerant in organic solvent due limited structure based information. The purpose of this study is to elucidate the three-dimensional structure of an organic solvent tolerant elastase. By investigating the structural-functions relationship of this organic solvent-tolerant enzyme using X-ray crystallography it will improve the understanding on elastase functionalities and its catalytic reactions. This recombinant elastase strain K was successfully purified to homogeneity by combination of hydrophobic interaction chromatography and ion exchange chromatography methods. Natively folded elastase of crystallisation-scale purity, quality and quantity was demonstrated and verified by SDS-PAGE, Native PAGE and Bradford assay analysis, respectively. Elastase strain K was also confirmed to be natively homogenous in size and uniformly-charge protein by observation of a single band in native-PAGE. The final protein content obtained after final purification step was 3 mg/mL Random crystal screening was performed using vapour diffusion methods and applied into various crystallisation formulation kits. The crystal formulation containing 1 M ammonium phosphate monobasic and 0.1 M sodium citrate tribasic dehydrate pH 5.6 shows a promising formulation producing elastase crystal. Microseeding technique has been chosen to improve the crystal hits. The highly purified elastase strain K with protein concentration around 3.00 mg/mL and pH 5.5 is the optimal condition for crystal growth. Besides, coupling seeding technique with capillary counter diffusion crystallization shows the improvement in size and diffraction quality of the crystals. The measurement of crystal size was 1 mm 0.1 mm 0.05 mm. Elastase strain K was successfully diffracted up to 1.39Å at SPring-8, Japan using synchrotron radiation. The space group has been determined to be P1211 belonged to the monoclinic space point with unit cell parameter was a = 38.99 Å, b = 90.173 Å, c = 40.60Ǻ. The structure of elastase strain K was refined and validated subsequently using PROCHECK and ERRAT. Crystal structure of elastase strain K showed the typical, canonical alpha-beta hydrolase fold consisting of 10-helices, 10- β-strands and other secondary structure of such as loop and coil. The elastase strain K is a zinc metalloproteinase possess His-140, His-144 and Glu-164 served as a ligand for zinc ion. The conserved catalytic triad was composed of Glu-141, Tyr-155 and His-223. Three-dimensional structure features such as calcium-binding and presence of disulphide-bridge contribute to the stabilizing the elastase strain K structure. In conclusion, the solvent-tolerant elastase strain K has been crystallised and the three-dimensional structure of elastase strain K was successfully elucidated. Information regarding unique properties followed by the structural features of this enzyme provides a useful insight towards rational design of enzymes stable in solvents